A Case of Influenza B and Mycoplasma pneumoniae Coinfection in an Adult. (25th November 2018) - Shinozaki, Taro; Sasahara, Kotaro; Iwami, Eri; Kuroda, Aoi; Matsuzaki, Tatsu; Nakajima, Takahiro; Terashima, Takeshi
Abstract : A 19-year-old woman was referred to our hospital because of a persistent fever and cough that lasted for over a week. Influenza B virus infection was diagnosed using the rapid test kit. Initially, the patient was diagnosed with influenza B infection associated with lobar pneumonia and treated with an anti-influenza virus drug and sulbactam/ampicillin. The patient's fever persisted, and her respiratory condition worsened. On day 5, a computed tomography (CT) scan revealed an extension of the consolidation areas in the left lung and new opacities in the right lung. The antibiotic treatment was changed to meropenem and levofloxacin, and the patient's physical condition gradually improved. A sputum sample revealed the presence of Mycoplasma pneumoniae -specific DNA. Both influenza B virus and M. pneumoniae infections were confirmed serologically. This was a case of coinfection with influenza B virus and M. pneumoniae in a healthy young woman. The M. pneumoniae pneumonia diagnosis was delayed because the predominant feature observed in the CT scan was dense consolidation. M. pneumoniae should be considered as one of the causative pathogens in influenza coinfection cases with CT scan images presenting dense consolidation.